Oil spill science and technology - Fingas, Mervin F. (Gulf Professional Publishing, 2017)
This book delivers a multi-contributed view on the entire chain of oil-spill related topics from oil properties and behaviors, to remote sensing through the management side of contingency planning and communicating oil spill risk perceptions.